Three dark crowns - Blake, Kendare (Harperteen, an imprint of HarperCollins Publishers, 2016)
In every generation on the island of Fennbirn, a set of triplets is born--three queens, all equal heirs to the crown and each possessor of a coveted magic. Mirabella is a fierce elemental, able to control storms or flames with the snap of her fingers. Katharine is a poisoner, able to ingest the deadliest poisons without harm. And Arsinoe, a naturalist, can control nature. But becoming the Queen Crowned isn't solely a matter of royal birth. Each sister has to fight for it. And it's not just a game of win or lose ... it's life or death. The night the sisters turn sixteen, the battle begins. The last queen standing gets the crown. --